(untitled) (Research, Society and Development, 2021)
Objective: To know the experiences, practices and challenges for the development of the School Health Program through Primary Health Care. Methodology: An integrative literature review study was conducted, the secondary databases used were the Virtual Health Library, Latin American and Caribbean Literature on Health Sciences (LILACS) and the Scientific Electronic Library Online (Scielo). The articles were searched with the descriptors School Health Services, Family Health Strategy and Primary Health Care. Results: Twenty-eight articles were found in the Virtual Health Library database, 63 in Scielo and 17 in LILACS, with the aid of inclusion and exclusion criteria, the final sample consisted of 17 articles. The School Health Program is a unique opportunity to approach the health and education sectors, being a strategy to promote students’ health, with numerous benefits. Final considerations: The actions developed in schools are punctual and unsystematic, only as responses to specific demands, which limits the scope of the actions of the School Health Program.